(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The present article conducts an analysis of tourism from the perspective of national values, positing its efficacy as a means for the implementation of cultural diplomacy. The potential for nations to showcase their culture, history, and values on the international stage is significant, and the influence of “soft power” through tourism can be a catalyst for strengthening diplomatic relations. The article examines the integration of national values into tourism policies, drawing upon examples from countries including Japan, Italy, India, Egypt, China, and Uzbekistan. Moreover, it engages with a range of ethical and moral issues, including the commercialization of cultural heritage, the preservation of authenticity, and the involvement of local communities. The article identifies the theoretical foundations, philosophical approaches, and practical development directions for tourism based on national values.